Biphasic increase in scratching behaviour induced by topical application of Dermatophagoides farinae extract in NC/Nga mice. Issue 8 (12th May 2016) - Yamada, Yoshihito; Ueda, Yuhki; Nakamura, Aki; Kanayama, Shoji; Tamura, Rie; Hashimoto, Kei; Kido, Hiroko; Matsumoto, Tatsumi; Ishii, Ritsuko
Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease accompanied by severe itching and eczematous lesion. In this study, we applied an ointment containing Dermatophagoides farinae body (Dfb) extract repeatedly on the dorsal skin of NC/Nga mice with barrier disruption to investigate the characteristics of this murine model of human AD. Following repeated topical application of Dfb ointment twice weekly for 2 weeks, the dermatitis score increased gradually, accompanied by an elevation of total immunoglobulin E level in plasma. Topical application of Dfb ointment also caused epidermal hyperplasia and accumulation of inflammatory cells in the lesional skin and increased expression of T‐helper (Th) 1/Th2/Th17 cytokines in axillary lymph node cells. Furthermore, increased sprouting of intraepidermal nerve fibres was observed with an increase in the content of nerve growth factor and decrease in that of semaphorin 3A in the lesional skin. These findings suggest that the characteristics in this model were similar to those observed in patients with AD. Interestingly, it was observed for the first time that scratching behaviour increased in a biphasic fashion by topical application of Dfb ointment in addition to an increase in spontaneous scratching behaviour in this model. It is also suggested that further clarifying the underlying mechanisms of scratching behaviour in this model leads not only to elucidating the pathogenesis of AD but also to discovering novel therapeutic drugs for AD.